Studies on Gonadosomatic Index (GSI) & Sex Ratio of Sind Sardine fish, Sardinella sindensis (Day, 1878) (Family: Clupeidae) of Karachi Coast, Pakistan. - Safi, Amtyaz; Hashmi, Usman Ali (International Journal of Biological Research, 2013)
The sex ratio & Gonadosomatic index of sind sardine, Sardinella sindensis (Day, 1878) of Karachi coast, Pakistan were investigated. Sardinella sindensis had sex ratio of 1: 1.25 (male to female). The difference in sex ratio was not significantly different (p > 0.05) from the expected theoretically 1: 1 distribution except April 2002. The highest Gonadosomatic index value in males during June – August were 3.813 to 4.078, while in females the high values during June – August were found to be 3.157 to 5.616, which suggested the spawning period. The highest GSI value in males were 2.548 to 2.711 in size groups of 170 – 199Mm and the lowest GSI value were 0.627 – 0.746 recorded in 110 – 129Mm, while in females at high values were 3.769 to 4.550 in 180 – 209 Mm Size groups and the lowest GSI values were 0.686 to 1.064 in 100 – 139 Mm size groups. The results will increase our knowledge of reproductive biology of Sardinella sindensis which is relevant for fisheries and aquaculture management as well as breeding programmes.